Roles of the bone marrow niche in hematopoiesis, leukemogenesis, and chemotherapy resistance in acute myeloid leukemia. Issue 10 (26th November 2018) - Wang, Andi; Zhong, Hua
ABSTRACT: Objectives: To summarize the effects of the bone marrow niche on hematopoiesis and leukemogenesis and discuss the chemotherapy resistance that can arise from interactions between the niche and leukemia stem cells. Methods: We review the major roles of the bone marrow niche in cell proliferation, adhesion and drug resistance. The signaling pathways and major molecular participants in the niche are discussed. We also address potential niche-targeting strategies for the treatment of acute myeloid leukemia (AML). Results: The bone marrow niche supports normal hematopoiesis and affects acute myeloid leukemia (AML) initiation, progression and chemotherapy resistance. Discussion: AML is a group of heterogeneous malignant diseases characterized by the excessive proliferation of hematopoietic stem and/or progenitor cells. Even with intensive chemotherapy regimens and stem cell transplantation, the overall survival rate for AML is poor. The bone marrow niches of malignant cells are remodeled into a leukemia-permissive environment, and these reformed niches protect AML cells from chemotherapy-induced cell death. Inhibiting the cellular and molecular interactions between the niche and leukemia cells is a promising direction for targeted therapies for AML treatment. Conclusions: Interactions between leukemia cells and the bone marrow niche influence hematopoiesis, leukemogenesis, and chemotherapy resistance in AML and require ongoing study. Understanding the mechanisms that underlie these interactions will help identify rational niche-targeting therapies to improve treatment outcomes in AML patients.